2003
DOI: 10.1091/mbc.e03-01-0012
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Raft Targeting of the TC10 Amino Terminal Domain Is Responsible for Disruption of Adipocyte Cortical Actin

Abstract: Overexpression of the Rho family member TC10alpha, disrupts adipocyte cortical actin structure and inhibits insulin-stimulated GLUT4 translocation when targeted to lipid raft microdomains. This appears to be independent of effecter domain function because overexpression of the wild-type (TC10/WT), constitutively GTP-bound (TC10/Q75L), and constitutively GDP bound (TC10/T31N) all inhibit adipocyte cortical actin structure and GLUT4 translocation. To examine the structural determinants responsible for these effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 79 publications
(66 reference statements)
0
10
0
Order By: Relevance
“…RHOQ also strongly differentiated VR-PAH from VN-PAH. This cytoskeletal gene facilitates protein transport and has been shown to be important in insulin-mediated signaling 29 , another pathway of importance in PAH 3032 . Of note, only EPDR1, UCHL1, DSG2, SCD5 and P2RY5 expression levels were elevated in VR-PAH compared with VN-PAH, and gene expression levels were more commonly suppressed in VR-PAH which may reflect underlying disease mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…RHOQ also strongly differentiated VR-PAH from VN-PAH. This cytoskeletal gene facilitates protein transport and has been shown to be important in insulin-mediated signaling 29 , another pathway of importance in PAH 3032 . Of note, only EPDR1, UCHL1, DSG2, SCD5 and P2RY5 expression levels were elevated in VR-PAH compared with VN-PAH, and gene expression levels were more commonly suppressed in VR-PAH which may reflect underlying disease mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…To test the effect of TC10 on the intracellular trafficking of CAL, we used confocal microscopy to examine the intracellular localization and distribution of CAL and TC10. Similar to H-ras, TC10 is synthesized by free ribosomes in the cytosol and then predominantly enters the conventional exocytic pathway from ER to Golgi en route to the plasma membrane (26,27). In transfected COS-7 cells, wild type HA-tagged TC10 is localized to the perinuclear secretory membrane compartments and the plasma membrane (Fig.…”
Section: Is the Expression Of Mature Cftr Proteinmentioning
confidence: 99%
“…The CAAX farnesylation motif is required for TC10 to enter the exocytic pathway from ER to Golgi. Upstream of CAAX sequence, a CXXC motif is found that functions in dual palmitoylation and plasma membrane targeting (26,27). Lovastatin, a 3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitor, blocks farnesylation (28,29).…”
Section: Is the Expression Of Mature Cftr Proteinmentioning
confidence: 99%
“…In 3T3-L1 adipocytes, overexpression of dominant-interfering TC10alpha mutant inhibits insulin-stimulated glucose uptake and GLUT4 translocation [ 82 , 89 ], suggesting the importance of GTPase activity in its function. On the contrary, another study shows that overexpression of TC10alpha or other chimeras with lipid raft-targeting motifs in adipocytes inhibits insulin-stimulated GLUT4 translocation, and these effects are independent of its GTPase activity but dependent on its membrane localization [ 90 ]. Furthermore, although siRNA-mediated TC10 knockdown was reported to effect insulin-simulated GLUT4 translocation, no other lab has reported the same findings and no mouse knockout models have corroborated these findings found in 3T3-L1 adipocytes.…”
Section: Temporal Regulators Of Insulin-stimulated Glut4 Translocamentioning
confidence: 99%